Comparison of the Preference Selection Index (PSI) Method with the Simple Additive Weight (SAW) Method in The Selection of the Best Foreman at PT. Agro Muko - Nurul Husna; Yupianti Yupianti; Reno Supardi (Penerbit Jurnal Indonesia, 2021)
PT. Agro Muko is a Foreign Investment Company engaged in oil palm and rubber plantations. Administratively, PT. Agro Muko is located between several sub-districts, namely North Mukomuko, South Mukomuko, Lubuk Pinang, Teras Terunjam, Pondok Suguh, V Koto, Penarik, Selagan Jaya, Air Dikit and Teramang Jaya Sub-Districts, Bengkulu Regency. For this reason, the researcher tried to build an application that compares the Preference Selection Index (PSI) Method with The Simple Additive Weight (SAW) Method on the selection of the best foreman using the Preference Selection Index (PSI) method using Visual Basic Net, in order to facilitate PT Agro muko in the selection of the best employee every year. Based on the results of the study, the comparison application of the Preference Selection Index (PSI) method with the Simple Additive Weight (SAW) method on the Best Foreman Selection at PT Agro Muko was made using Visual Basic Net programming language with SQL server database as a supporting medium, storing the results of data processing that can be used. used by PT Argo Muko in inputting employee data, so that later it can help in overcoming existing problems so that the process of selecting the best foreman can be done using the application.